Computed tomography characteristics of equine paranasal sinus cysts. (12th February 2020) - Ostrowska, Justyna; Lindström, Lisa; Tóth, Tamás; Hansson, Kerstin; Uhlhorn, Margareta; Ley, Charles J.
Abstract: Background: Computed tomography (CT) is commonly used to investigate equine paranasal sinus disease, however, only limited information is available in the literature about the detailed CT appearance of equine paranasal sinus cysts. Objectives: To investigate if paranasal sinus cysts have specific characteristics in CT images that allow differentiation from other sinus diseases. Study design: Retrospective observational study. Methods: Evaluation and comparison of CT studies of eight horses with surgically and/or histopathologically confirmed paranasal sinus cysts and 10 horses with other confirmed paranasal sinus diseases. Results: A discrete hyperattenuating wall‐like structure was detected in the periphery of the sinus lesion in precontrast acquisition in 7/8 horses with paranasal sinus cysts. A similar wall‐like structure was detected in 3/10 horses with other sinus diseases, however, in contrast to horses with paranasal sinus cysts, two of these also had hyperattenuating regions within the contents of the sinus lesion. Bone destruction and formation affecting cancellous and cortical bone and dental disease were frequent in horses with paranasal sinus cysts. No significant difference in attenuation values was found when the fluid/soft tissue attenuation contents of lesions in horses with paranasal sinus cysts (mean 28.9 ± SD 9.2 HU) were compared with other sinus diseases when ethmoid haematomas were excluded (30.4 ± 12.9 HU, P  = .8). Main limitations: Low number of cases. Conclusions: Detection of a hyperattenuating cystic wall is a helpful feature for identifying paranasal sinus cysts in CT images of horses. In contrast, measurement of attenuation values of the soft tissue/fluid contents of the sinus lesions was not helpful in identifying paranasal sinus cysts.